The reliability of insertion torque as an indicator for primary stability in immediate dental implant: A prospective clinical study - Ikhlas A Dkheel; Ahmed F Al-Quisi; Noura AlOtaibi (College of Dentistry/ University of Baghdad, 2024)
Background: The primary stability of the dental implant is a crucial factor determining the ability to initiate temporary implant-supported prosthesis and for subsequent successful osseointegration, especially in the maxillary non-molar sites. This study assessed the reliability of the insertion torque of dental implants by relating it to the implant stability quotient values measured by the Osstell device. Material and methods: This study included healthy, non-smoker patients with no history of diabetes or other metabolic, or debilitating diseases that may affect bone healing, having non-restorable fractured teeth and retained roots in the maxillary non-molar sites. Primary dental implant stability was evaluated using a torque ratchet from the dental implant kit and ISQ values generated from the Osstell device. Results: Twenty patients (13 female and 7 male) with an age range of 25-65 years received twenty immediate dental implants. The insertion torque value ranged from 15 to 50 N/cm with a mean of 28 N/cm. At the same time, the ISQ values ranged between 50 and 80 ISQ values, with a mean of 63 ISQ values. The results showed a statistically significant positive correlation between the insertion torque of the dental implant measured by torque rachet and ISQ values checked with Osstell. Conclusion: The insertion torque can be used as a reliable method to estimate the primary stability of the immediately inserted dental implants in the maxillary non-molar sites comparable to the Osstell device ISQ values. In addition, torque ratchet is readily available in the dental implant kit at no additional cost, making it a valuable choice over the Osstell device.